Affinity of Nintedanib Towards New Candidate Target for Idiopathic Pulmonary Fibrosis - Balasubramanian, Hari Baskar; Biswas, Sima; Talmon, Maria; Patrucco, Filippo; Balbo, Piero Emilio; Fresu, Luigia Grazia; Bagchi, Angshuman (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2024)
Idiopathic pulmonary fibrosis (IPF) is a progressive disease due to aggregation of fibroblasts on lung parenchyma. Nintedanib, an indolinone-derived tyrosine kinase inhibitor (TKi) has been approved for the treatment of IPF and it is a well-known inhibitor of platelet-derived growth factor (PDGF) receptor-α and -β, fibroblast growth factor (FGF) receptor-1–3 and vascular endothelial growth factor (VEGF) receptor-1–3. This study aims to evaluate the binding interaction between new therapeutic protein candidates for IPF such as autotaxin, galectin-3, interleukin-13, chitotriosidase-1, JNK, RhoE-ROCK-1, ROCK-2 against nintedanib. In this investigation we predicted, computed, and analyzed the binding interactions of the drug nintedanib using an in silico approach called molecular docking. Our docking studies demonstrated that RhoE-ROCK1 and autotaxin showed strong binding affinities towards nintedanib compared to known targets such as VEGFR2 and FGFR1. We can therefore hypothesize a further contribution of nintedanib to the improvement of pathology due to its affinity towards new targets in the pathogenesis of IPF. The next step will be to evaluate the effects of this affinity in vitro on specific cellular models.